Features of Management of the Russian Investment and Construction Projects - V. I. Resin; S. S. Bachurina; N. D. Korjagin; A. I. Sukhorukov; S. Yu. Eroshkin (Мир новой экономики, 2018)
This article provides an overview of the key English terms used in the information support of modern development. Identified the key information systems used in the development in accordance with their hierarchy, and shows the basic control information flows. The tendencies of development of systems management of construction projects in the General system of the global network economy. It justifies the approach of system development of information tools of management of investment-construction projects of complex infrastructure projects throughout their lifecycle from project initiation to disposal of the object. Examples of the major manufacturers of software for information management, which use aggregation of information flows and integrate management decisions into a single global system.